1994
DOI: 10.1007/bf02076192
|View full text |Cite
|
Sign up to set email alerts
|

Delorme's procedure for complete rectal prolapse in severely debilitated patients

Abstract: Satisfactory prolapse repair was safely performed in 78 percent of this high-risk group. Pitfalls in performing this procedure relate primarily to associated perineal and colonic conditions. Most prominent among these conditions are weak or absent and sphincter tone, perineal descent, and previous sphincter injury. Extensive diverticular disease may prohibit effective and complete proximal mucosectomy. An inadequate mucosectomy sets the stage for early recurrence of prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
9

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 10 publications
0
53
0
9
Order By: Relevance
“…In our series, the recurrence rate was quite low and it was reported at the level of 8.7 %. Although Oliver et al [23] reported a general improvement in continence, likely obtained by the plication of muscularis propria of the rectal wall, we did not assess the clinical severity of incontinence either prior or following surgery, and only in our series, manometric findings revealed no improvement in anal sphincter function in the group.…”
Section: Discussionmentioning
confidence: 60%
“…In our series, the recurrence rate was quite low and it was reported at the level of 8.7 %. Although Oliver et al [23] reported a general improvement in continence, likely obtained by the plication of muscularis propria of the rectal wall, we did not assess the clinical severity of incontinence either prior or following surgery, and only in our series, manometric findings revealed no improvement in anal sphincter function in the group.…”
Section: Discussionmentioning
confidence: 60%
“…They concluded that Delorme's procedure combined with sphincteroplasty seemed indicated when both clinical and physiological findings showed a concomitant severe pelvic floor dysfunction. However, many other series without sphincteroplasty have shown improvement in continence [9,[12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Oliver et al [14] successfully performed Delorme's procedure in 41 patients. They pointed out that important pitfalls in performing the procedure were weak or absent sphincter tone, perineal descent, and previous sphincter injury.…”
Section: Discussionmentioning
confidence: 99%
“…Oliver et al [10] performed the Delorme procedure in 41 patients who were deemed unfit for major surgery because of age or comorbidity. They found that the important difficulties in performing the procedure were weak or absent sphincter tone, perineal descent, and previous sphincter injury.…”
Section: Discussionmentioning
confidence: 99%